2020
DOI: 10.1108/jhtt-08-2019-0107
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of the fourth industrial revolution for the hospitality industry: a literature review

Abstract: Purpose The economy of today has moved toward the fourth industrial revolution (FIR), which is characterized by the adoption of technologies such as cyber-physical systems, internet of things, big data, artificial intelligence and robotics. Globally, there is a lot of awareness created on the influence of the FIR on all industries, including hospitality and tourism. A plethora of studies on FIR have been conducted in the setting of manufacturing industries. Nonetheless, there seems to be in-exhaustive and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(98 citation statements)
references
References 29 publications
(87 reference statements)
1
46
0
Order By: Relevance
“…Here are the top emerging technologies being deployed in the supply chains: the 3D printer (Chiarini et al, 2020;Ferdows, 2018;Kothman and Faber, 2016;Nascimento et al, 2019;Naveh and Lei, 2019;Tortorella et al, 2019), the additive manufacturing (Alabi et al, 2019;Handal, 2017;Kang et al, 2016;Ramirez-Peña et al, 2020b), the artificial intelligence (Osei et al, 2020;Rajput and Singh, 2019b;Ramirez-Peña et al, 2020b), the augmented reality (Ramirez-Peña et al, 2020b), the autonomous robots (Ramirez-Peña et al, 2020b), the autonomous vehicles (Gru zauskas et al, 2018;Perussi et al, 2019), the big data (Ardito et al, 2019b;Bag and Pretorius, 2020;Bertola and Teunissen, 2018;Chalmeta and Santos-de Le on, 2020;Chiappetta Jabbour et al, 2020;Chiarini et al, 2020;Del Giudice et al, 2020;Dutta et al, 2020;Fagundes et al, 2020;Gottge et al, 2020;Kadi and Keivanpour, 2018;Li et al, 2020a, b;Mart ın-G omez et al, 2019;Mastos et al, 2020;Montes and Olleros, 2020;Naveh and Lei, 2019;Osei et al, 2020;Pham et al, 2019a;Queiroz and Telles, 2018;Rajput and Singh, 2019a;Ramirez-Peña et al, 2020b;Sardi et al, 2020;Singh and Kumar, 2020;…”
Section: 3mentioning
confidence: 99%
“…Here are the top emerging technologies being deployed in the supply chains: the 3D printer (Chiarini et al, 2020;Ferdows, 2018;Kothman and Faber, 2016;Nascimento et al, 2019;Naveh and Lei, 2019;Tortorella et al, 2019), the additive manufacturing (Alabi et al, 2019;Handal, 2017;Kang et al, 2016;Ramirez-Peña et al, 2020b), the artificial intelligence (Osei et al, 2020;Rajput and Singh, 2019b;Ramirez-Peña et al, 2020b), the augmented reality (Ramirez-Peña et al, 2020b), the autonomous robots (Ramirez-Peña et al, 2020b), the autonomous vehicles (Gru zauskas et al, 2018;Perussi et al, 2019), the big data (Ardito et al, 2019b;Bag and Pretorius, 2020;Bertola and Teunissen, 2018;Chalmeta and Santos-de Le on, 2020;Chiappetta Jabbour et al, 2020;Chiarini et al, 2020;Del Giudice et al, 2020;Dutta et al, 2020;Fagundes et al, 2020;Gottge et al, 2020;Kadi and Keivanpour, 2018;Li et al, 2020a, b;Mart ın-G omez et al, 2019;Mastos et al, 2020;Montes and Olleros, 2020;Naveh and Lei, 2019;Osei et al, 2020;Pham et al, 2019a;Queiroz and Telles, 2018;Rajput and Singh, 2019a;Ramirez-Peña et al, 2020b;Sardi et al, 2020;Singh and Kumar, 2020;…”
Section: 3mentioning
confidence: 99%
“…Lodging facilities have started to invest in Web 3 and smart technologies to enhance interoperability, accelerate innovation and personalize customer experience (Osei et al , 2020). Empirical studies showed conflicting findings about relationship between IT investment and a company’s productivity and performance, which led to the IT Productivity Paradox (Kobelsky et al , 2008).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Cyber-physical systems are one of the key enabling technologies of Industry 4.0. Cyber-physical systems are able to effectively support the optimization of production processes, which helps future requirements to be met [3].…”
Section: Introductionmentioning
confidence: 99%